2016
DOI: 10.3758/s13421-016-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

The diversity effect in diagnostic reasoning

Abstract: Diagnostic reasoning draws on knowledge about effects and their potential causes. The causal-diversity effect in diagnostic reasoning normatively depends on the distribution of effects in causal structures, and thus, a psychological diversity effect could indicate whether causally structured knowledge is used in evaluating the probability of a diagnosis, if the effect were to covary with manipulations of causal structures. In four experiments, participants dealt with a quasimedical scenario presenting symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Related terms in psychology include clinical decision-making, 122 diagnosis. [123][124][125][126][127][128][129][130] Related concepts and antecedents directed at cues, 122,123,131 key features, 132 hypothesis testing [127][128][129]133 and statements made or a situation presented. 126,133,134 The consequence was a formed judgement 125,127,[135][136][137] and attributes included critical thinking, 122,134,136,[138][139][140][141][142][143] reflection, 141 weighing information, 132 flexibility in thinking.…”
Section: [Hd2]synopses Of Clinical Reasoning By Disciplinementioning
confidence: 99%
See 2 more Smart Citations
“…Related terms in psychology include clinical decision-making, 122 diagnosis. [123][124][125][126][127][128][129][130] Related concepts and antecedents directed at cues, 122,123,131 key features, 132 hypothesis testing [127][128][129]133 and statements made or a situation presented. 126,133,134 The consequence was a formed judgement 125,127,[135][136][137] and attributes included critical thinking, 122,134,136,[138][139][140][141][142][143] reflection, 141 weighing information, 132 flexibility in thinking.…”
Section: [Hd2]synopses Of Clinical Reasoning By Disciplinementioning
confidence: 99%
“…[124][125][126][127][128][129]133,[143][144][145] Many of the psychology articles were primarily discussing medical reasoning related to physician diagnoses and problem solving. 124,125,129,130 Those articles that focused specifically on psychology related clinical reasoning to critical thinking and logical problem solving. 122,138,140,144 Related terms in the health professions (PT, OT) literature included critical thinking and decision-making.…”
Section: [Hd2]synopses Of Clinical Reasoning By Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…The sequential integration of information enables the retrieval of critical information from memory to generate and evaluate the best causal explanation. Recent research on this subject has shown that this generation and evaluation process depends on the activation of information from long-term memory (Mehlhorn et al, 2011; Rebitschek et al, 2016; Thomas et al, 2008). In a study by Mehlhorn et al (2011), participants first learned associations between medical symptoms and potential chemicals that caused them (and therefore act as their explanations).…”
Section: Introductionmentioning
confidence: 99%
“…To form a correct situation model, is it necessary to have all previous information active in memory, according to research showing that the generation of explanations is influenced by the knowledge currently activated in memory (Mehlhorn, Taatgen, Lebiere, & Krems, 2011;Rebitschek, Krems, & Jahn, 2016;Thomas, Dougherty, Sprenger, & Harbison, 2008). Based on the situation model, the reasoner forms explanations of the observation.…”
Section: The Reasoning Processmentioning
confidence: 99%